Imperfect Solidarities - Madhumita Lahiri (Northwestern University Press, 2020)
A century ago, activists confronting racism and colonialism-in India, South Africa, and Black America-used print media to connect with one another. Then, as now, the most effective medium for their undertakings was the English language. Imperfect Solidarities: Tagore, Gandhi, Du Bois, and the Global Anglophone tells the story of this interconnected Anglophone world. Through Rabindranath Tagore's writings on China, Mahatma Gandhi's recollections of South Africa, and W.